REAKSI PASAR TERHADAP KEBIJAKAN PEMBERLAKUAN PEMBATASAN KEGIATAN MASYARAKAT (PPKM) LEVEL 4 PADA PERUSAHAAN LQ-45 YANG TERDAFTAR DI BURSA EFEK INDONESIA - Devinda Larasati; Nur Diana; Arista Fauzi Kartika Sari (Universitas Islam Malang, 2022)
The purpose of this research was to determine the market reaction to Trading Volume Activity and Stock Returns before and after the implementation of Level 4 Community Activity Restrictions (PPKM) on LQ-45 companies listed on the Indonesia Stock Exchange. Quantitative research design was adopted in this study, this study collected secondary data. This study used a purposive sampling method and the number of participants was 43 LQ-45 companies listed on the IDX for 20 days before and 20 days after the implementation of the restriction on community activities (PPKM) Level 4. Hypothesis testing was carried out using a paired sample t test. The results of this study based on hypothesis testing on a paired sample t test showed that the average stock return before and after the announcement of PPKM Level 4 showed an asymptotic significance value (2-tailed) of 0.986. The value is > 0.05 which means there is no significant difference between before and after the implementation of PPKM Level 4 on Stock Return. And the average Trading Volume Activity (TVA) before and after the announcement of PPKM Level 4 showed an asymptotic significance value (2-tailed) of 0.013. The value is < 0.05 which means there is a significant difference between before and after the implementation of PPKM Level 4 on Trading Volume Activity (TVA).Keywords: Trading Volume Activity, Return Saham, Level 4 Community Activity Restrictions